Effect of self-heating during processing of rigid and plasticized poly(vinyl chloride) on its thermal stability - Simonov-Emelianov, I. D.; Markov, A. V.; Prokopov, N. I.; Gritskova, I. A.; Munkin, N. I.; Hexel, L. (Polimery, 2013)
Times of dynamic thermal stability ( t) depending on real temperatures of poly(vinyl chloride) (PVC) melts with different viscosities were investigated and compared. The experimental data were analyzed using the Arrhenius equation and the activation energy of PVC dehydrochlorination was determined. It was found that increased thermal stability of the melts caused by plasticization is related to a decrease in their self-heating.